TINMAN AND BAGPIPE - 2 HOMEO BOX GENES THAT DETERMINE CELL FATES IN THE DORSAL MESODERM OF DROSOPHILA - Azpiazu, Natalia; Frasch, Manfred (Genes & Development, 1993)
Whereas the mechanisms of early Drosophila mesoderm formation have been studied in much detail, the subsequent processes determining regional identities within the mesoderm remain largely unknown. Here, we describe two homeo box genes, tinman (tin) and bagpipe (bap), which spatially subdivide the mesoderm and determine cell fates in the dorsal mesoderm. These two genes are components of a cascade of genetic interactions that result in the spatial restriction of tin mRNA to the dorsal mesoderm and in the activation of bap in segmental clusters of cells in this region. A subset of cells from those clusters segregate to form visceral mesoderm that differentiates into gut musculature. This indicates that the visceral mesoderm is derived from metamerically repeated primordia. In embryos mutant for bap, visceral mesoderm formation is strongly disrupted. Most cells of the visceral mesoderm fail to differentiate properly, and a portion of them are transformed into body wall musculature and gonadal mesoderm. In tin mutant embryos, bap expression is not activated in the dorsal mesoderm. Probably as a consequence, neither visceral mesoderm nor midgut musculature are formed in these mutants, and the absence of visceral mesoderm results in strong disruptions of endoderm migration and midgut morphogenesis. In addition to visceral mesoderm development, tin is required for the formation of the heart from dorsal mesoderm and for the specification of founder cells for particular body wall muscles.
Keywords: DROSOPHILA DORSAL MESODERM; HOMEO BOX GENES; TINMAN; BAGPIPE; CELL FATE